"It's an Ongoing Bromance": Counterculture and Cyberculture in Silicon Valley—An Interview with Fred Turner. (April 2021) - Lusoli, Alberto; Turner, Fred
Fred Turner is considered one of the most influential experts on, and critical observers of, cyberculture. He is Harry and Norman Chandler Professor of Communication at Stanford University in the Department of Communication. Through his work, he provided a thoughtful analysis of the politics and culture of Silicon Valley. In his books, he explored the connections between the collaborative and interdisciplinary research culture of the Second World War, the protest movements of the 1960s, and the managerial ethos permeating digital and new media industries. In this interview, we discuss about the consequences that the countercultural movements had on the organization of labor in modern tech giants, especially in relation to the substitution of hierarchies for flat and more entrepreneurial structures. We also talk about the consequences that a code of ethics might have in the democratization of technology and the responsibility that we have as citizens and academics.